Synthesis and application of a new antibacterial surfactant from apricot kernel oil - Hanaa M. Soliman (Scientific Reports, 2023)
Abstract Food emulsifier are mostly prepared from a lipophilic lipid tail with a hydrophilic sugar head. In this study, the lipophilic tail was obtained from apricot kernels, which are food waste, and the hydrophilic head was gluconic acid instead of sugar, in order to draw attention to the non-cyclic poly hydroxyl compounds. Thus, oleic acid of apricot kernel was used as the lipophilic moiety of the prepared surfactant. So, apricot kernel was grinned and dried, oil was extracted using soxhlet apparatus, Physical and chemical parameters and fatty acids composition of the extracted oil had been determined. The extracted oil was then hydrolyzed into glycerol and a mixture of free fatty acids. The fatty acids mixture was separated. Then, oleic acid was extracted individually in pure form using supercritical CO2 extractor, it was then confirmed according to its melting point, Gas chromatography–mass spectrometry (GC–MS) after esterification, elemental analysis, Proton nuclear magnetic resonance (H1NMR), and mass spectrometry (MS) to detect the corresponding molecular ion peak. The pure individual oleic acid was converted to hydroxy stearic acid, which was then converted to an amphiphilic compound (surfactant) via esterification reaction with the hydrophilic gluconic acid, and afforded a new surfactant known as 2,3,4,5-tetrahydroxy-6-((9-((-2,3,4,5,6-pentahydroxyhexanoyl) oxy)octadecanoyl) oxy)hexanoic acid or stearyl gluconate for simplification. The structures elucidation of all synthesized compound was established according to elemental analysis and spectral data (Fourier transform infrared IR, 1H NMR, 13C NMR and MS). Moreover, the prepared compound was tasted for its antibacterial activity, and showed good activities against some types of bacteria. The surface-active properties, foamability, foaming stability and emulsion stability of stearyl gluconate were studied and compared with the properties of the well-known surfactant sucrose stearate, and it was clear that, the activity of stearyl gluconate as a surfactant was higher than that of sucrose stearate. Moreover, establishment of safety of this compound was performed using albino rats by acute oral toxicity and kidney and liver functions of these mice. On the other hand, the prepared surfactant was used in the production of low fat—free cholesterol mayonnaise as egg replacer. Texture properties and the sensory evaluation of the prepared mayonnaise showed that the properties were improved by using the new prepared surfactant. Thus, the prepared gluconyl stearate can be used as a safe food additive.